LPI Based Earthquake Induced Soil Liquefaction Susceptibility Assessment at Probashi Palli Abasan Project Area, Tongi, Gazipur, Bangladesh - Farazi, A. H.; Ferdous, N.; Kamal, A. S. M. M. (Journal of Scientific Research, 2018)
This study aims at evaluation of seismic soil liquefaction hazard potential at Probashi Palli Abasan Project area of Tongi, Gazipur, exploiting standard penetration test (SPT) data of 15 boreholes, following Simplified Procedure. Liquefaction potential index (LPI) of each borehole was determined and then cumulative frequency distribution of clustered LPI values of each surface geology unit was determined assuming cumulative frequency at LPI = 5 as the threshold value for liquefaction initiation. By means of geotechnical investigation two surface geological units—Holocene flood plain deposits, and Pleistocene terrace deposits were identified in the study area. We predicted that 14% and 24% area of zones topped by Pleistocene terrace deposits and zones topped by Holocene flood plain deposits, respectively, would exhibit surface manifestation of liquefaction as a result of 7 magnitude earthquake. The engendered hazard map also depicts site specific liquefaction intensity through LPI values of respective boreholes, and color index, which was delineated by mapping with ArcGIS software. Very low to low, and low to high liquefaction potential, respectively, was found in the areas covered by Pleistocene terrace deposits and Holocene flood plain deposits. LPI values of both units are such that sand boils could be generated where LPI > 5.